Mechanistic studies of an L-proline-catalyzed pyridazine formation involving a Diels–Alder reaction with inverse electron demand - Schnell, Anne; Willms, J. Alexander; Nozinovic, S.; Engeser, Marianne (Beilstein Journal of Organic Chemistry, 2019)
The mechanism of an L-proline-catalyzed pyridazine formation from acetone and aryl-substituted tetrazines via a Diels–Alder reaction with inverse electron demand has been studied with NMR and with electrospray ionization mass spectrometry. A catalytic cycle with three intermediates has been proposed. An enamine derived from L-proline and acetone acts as an electron-rich dienophile in a [4 + 2] cycloaddition with the electron-poor tetrazine forming a tetraazabicyclo[2.2.2]octadiene derivative which then eliminates N2 in a retro-Diels–Alder reaction to yield a 4,5-dihydropyridazine species. The reaction was studied in three variants: unmodified, with a charge-tagged substrate, and with a charge-tagged proline catalyst. The charge-tagging technique strongly increases the ESI response of the respective species and therefore enables to capture otherwise undetected reaction components. With the first two reaction variants, only small intensities of intermediates were found, but the temporal progress of reactants and products could be monitored very well. In experiments with the charge-tagged L-proline-derived catalyst, all three intermediates of the proposed catalytic cycle were detected and characterized by collision-induced dissociation (CID) experiments. Some of the CID pathways of intermediates mimic single steps of the proposed catalytic cycle in the gas phase. Thus, the charge-tagged catalyst proved one more time its superior effectiveness for the detection and study of reactive intermediates at low concentrations.
Keywords: charge-tag; electrospray ionization; enamine organocatalysis; L-proline; reaction mechanism